Bionomics of the unexplored sand flies fauna of District Mohmand, Khyber Pakhtunkhwa, Pakistan: assessing risk factors associated with cutaneous leishmaniasis. (23rd April 2022) - Khan, Khurshaid; Sajjad, Muhammad; Wahid, Sobia; Gul, Muhammad; Khan, Luqman; Ullah, Haseen; Rahman, Yasin; Khan, Dawood; Khan, Kashif; Khan, Muhammad Younas; Khan, Saqib; Shah, Safeer Ullah
Abstract: Background: Sand flies are of considerable public health importance in Pakistan because these insects are vectors of leishmaniasis. The current study explores the bionomics of sand flies, their spatial distribution pattern and cutaneous leishmaniasis-associated risk factors in District Mohmand, Khyber Pakhtunkhwa, Pakistan. Methods: Sand flies were collected from indoor and outdoor habitats in 69 villages of five tehsils in Mohmand during July–October 2019. Risk factor data were recorded for 829 households in 94 villages. Results: In total, 2065 sand flies were captured. Phlebotomus (Paraphlebotbmus) sergenti was the most abundant species. Relative density for P. sergenti and Phlebotomus papatasi was highest in Prang Ghar and lowest in Safi. Sand flies abundance peaked in August and September, corresponding to maximum relative humidity, temperature and rainfall. Relative density for P. sergenti and P. papatasi was highest in combined dwellings (indoor) and cattle corrals (outdoor). Phlebotomus sergenti and P. papatasi were abundant at an elevation of 283–1140 m on agricultural land and rangelands. Both species were recorded abundantly on Carbontites, Mesozoic and Indus suture Melange rock formations. Presence of domestic animals, ownership of pet dogs, presence of muddy dunes in the village, knowledge of sandflies and use of mosquitoes spray remained significant risk factors. Conclusions: The study reports sand fly bionomics in District Mohmand. Risk identified for cutaneous leishmaniasis are significant in strategising control methods for Health authorities can allocate localized control means to high-risk areas using these findings.